Duration of New-Onset Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Seizure duration was determined in a prospective study of 407 children with a first unprovoked seizure treated at the Epilepsy Management Center, Montefiore Medical Center, Bronx, NY.